Comparative study of zooid and non-zooid forming strains of Scenedesmus obliquus. Physiology and cytomorphology - Cepák, V; Pribyl, P; Kvíderová, J; Lukavský, J (Folia microbiologica, 2006)
Two zooid forming strains and four non-zooid strains of the green chlorococcal alga Scenedesmus obliquus were compared in terms of growth, morphological and physiological characteristics. Large differences were observed among the strains grown under various growth conditions (light and temperature). The assumption that the zooid forming strains may be similar was not confirmed. Since they considerably differed in daughter cells morphology, photosynthesis, growth rate in batch culture or commitment to cellular division. Molecular-genetic comparison of 18S RNA/DNA might distinguish zooid forming strains from non-zooid ones.
Keywords: Photosynthesis; Light; Chlorophyll; Scenedesmus; pohyb buněk; chlorofyl; koncentrace vodíkových iontů; fotosyntéza; spory; světlo; buněčný cyklus; Cell Cycle; Spores; vysoká teplota; Hot Temperature; Hydrogen-Ion Concentration; Cell Movement